Regulating the size of antimony nanoparticles to enhance the photo-response in the near-infrared region and anti-hepatoma cell activity - Huang, Lingling; Gong, Yimin; Chen, Zhijian; Tan, Yanjun; Gao, Qian; Wang, Yilei; Gao, Yuyu; Cheng, Wanting; Liang, Weiyuan; Yang, Xiaoli (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionAntimony (Sb) has been used as a medication for centuries, while it has rarely been investigated in plasmonic phototherapy, partly due to the lack of effective liquid-phase controllable synthesis methods to construct Sb nanocrystals with an optimized absorption curve within the biological transparent window (near-infrared region), achieving more effective and less side-effect phototherapy.MethodsHerein, an effective ligand-guided growth strategy was employed to synthesize Sb nanoparticles (Sb NPs) with high photothermal conversion efficiency (PTCE). The spatial electric field distribution of Sb NPs was simulated by the finite-difference time-domain (FDTD) method to validate their localized surface plasmon resonance (LSPR) effect. Sb NPs were coated with polydopamine (PDA) and polyethylene glycol (PEG) to enhance their biocompatibility. The synergistic anti-hepatoma activities of Sb NPs were evaluated via in vitro experiments.ResultsSb NPs were successfully obtained via a ligand-guided growth strategy. Uv-vis absorption peak was observed to red-shift from 520 nm to 810 nm as the size of Sb NPs increased from 40 nm to 70 nm. Sb NPs achieve a PTCE of 59.3% under 808 nm resonant excitation and was favorable to photothermal therapy (PTT). Sb NPs also exhibit 660 nm laser responsiveness, producing reactive oxygen species (ROS) that enable photodynamic therapy (PDT). In vitro anti-BEL-7404 hepatoma cells experiments revealed that 660 nm/808 nm laser irradiation could inhibit proliferation, promote apoptosis, and induce G2/M phase blockage tendency, with combined irradiation exhibiting more significant effects.ConclusionThe fabricated Sb-PDA exhibits synergistic PTT/PDT potential, though its in vivo efficacy and mechanisms warrant deeper investigation. LSPR-induced Sb-based nanomedicine may unlock diverse biomedical applications of semimetals.